Identifying Biases and the Relevant Statistical Population: The Case of the Loch Ness Monster - Charles G. M. Paxton; Adrian J. Shine; Valentin M. Popov (Journal of Statistics and Data Science Education, 2025)
We used a database of Loch Ness Monster reports to show university level students how important it is to think about bias and the identification of the correct statistical population. The Loch Ness Monster reports database illustrates the importance of considering independence, inaccuracy and imprecision when considering data and how statisticians might handle anecdotes as data. Whilst the data is inappropriate for directly making inferences about Loch Ness Monsters, it may be appropriate for making inferences about the population of Loch Ness Monster reports.